High performance liquid chromatography mass spectrometric (LC-MS/MS) method for the estimation of clopidogrel bisulfate in human plasma by liquid-liquid extraction technique - Shaban G. Elosta; Mohamed H. Assaleh (International Journal of Pharmacy and Analytical Research, 2022)
A high performance liquid chromatography mass spectrometric method for the estimation of clopidogrel (CLP), in human plasma in positive ion mode was developed and validated using clopidogrel D3 (CLPD) as internal standard (IS). Sample preparation was accomplished by liquid-liquid extraction technique. The reconstituted samples were chromatographed on Kromasil 100-5C18, 100×4.6 mm, 5µm column using a mobile phase consisting of HPLC grade Acetonitrile: Milli Q/HPLC grade water (90:10, v/v). The method was validated over a concentration range of0.0101 to 5.0315 ng/mL for CLP. This validation report provides the results of selectivity, matrix effect, sensitivity determinations, calibration standards and quality control samples data, precision and accuracy data, the results of recovery, various stabilities, run size evaluation and dilution integrity along with all pertinent supporting documentation.